Complex exodontics of third molar lower in invested position. Case Report - Lara, Vladimir (2019)
The aim of this study is to explain and demonstrate the surgical exodoncy of the lower thir molar in the inverted position. The present case concerns a 30 years old male patient without relevant medical history, attended SERODU dental clinic. The radiographic and tomographic examination showed that part # 38 is in an inverted position, so it was decided to carry out the extraction of the inverted third lower molar since they were free of pathology and by orthodontic indications. indications of orthodontics. At 8 days after the surgical procedure, the stitches are removed and soft tissue healing, absence of pain, edema and infection are clinically observed. The impact of the lower third molars inverted up to the present has been very little evidenced by finding very few cases on this subject, for this reason we believe that our clinical case would be an important help on the diagnosis and surgical treatment of this type of dental impacts.